Вірш Василя Стуса "Дозволь мені сьогодні близько шостої...": спроба орфічно-просторового аналізу одного сновиддя - Пучков, А.О. (Слово і Час, 2019)
Здійснено “повільне прочитання” вірша Василя Стуса “Дозволь мені сьогодні близько шостої…” (1975 – 1979) з метою виявлення конотативних мотивів історико-культурного й предметно-просторового плану. Показано, що карбування цих мотивів за допомогою іменників (образ), прикметників і дієслів (мотив) породжують у свідомості читача не так художній простір, спрямований на формування “художнього образу”, як архітектонічний простір (сюжет), задля унаочнення дій, що ними зумовлено (або їм підпорядковано) смислову конструкцію вірша. Виявлено, за допомогою яких саме образних засобів у вірші подано просторові конструкції й окреслено часові моменти. Прояснено наявність міфічного мотиву Орфея й Еврідіки, що властиво творчій свідомості Стуса. The paper presents an attempt to slowly read the poem by Vasyl Stus “Let me about sixth today…” (1975 – 1979) in order to identify connotative motifs of historical, cultural and subject-spatial nature. It is shown that the fixation of these motifs with the help of nouns (image), adjectives and verbs (motive) generates in the reader’s mind not so much an artistic space aimed at forming an “artistic image” as an architectonic space (plot) aimed at depicting the actions that cause (or subject to them) the semantic construction of the poem. The research methodology is based on the classical method of analyzing a poem, a comparative statistical one, which was proposed and developed by Boris Yarkho and Mikhail Gasparov. Counting nouns is carried out within such groups of them: objects; abstract concepts of the external world; abstract concepts of the inner world; appearance. The use of nouns made it possible to see that all concepts meaning things are subject to the compilation of a certain landscape or – more broadly – a space saturated with par excellence negative visual stimuli that one doesn’t want to notice. The figurative means of the poem that form spatial constructions and show temporal characteristics are indicated. The researcher explains the presence of the mythical motive of Orpheus and Eurydice, being characteristic for the creative consciousness of the poet. However, it looks like Stus changes the roles of Eurydice and Orpheus. In using the reverse perspective technique one should see Kyiv as a place of mythological events, akin to Hellenic, but, despite all the toponymic specifics, it lacks positive features: the anxiety of the myth about Eurydice is reflected here as well. The imprisonment of a hero is directly associated with the kingdom of Persephone and Hades. But the model is somewhat complicated: the reason of Orpheus’ anxiety in the ancient myth is somewhat obscure, while in the poem by Stus the hero really worries not so much about his beloved as due to eventual anxiety for his beloved, and therefore about her and her son.